2015
DOI: 10.1007/s00253-015-6807-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of antibody production in Saccharomyces cerevisiae: effects of ER protein quality control disruption

Abstract: One of the main limitations for heterologous protein production in the yeast Saccharomyces cerevisiae is the protein folding capacity in the endoplasmic reticulum (ER). Accumulation of unfolded proteins triggers the unfolded protein response (UPR), which resolves the stress by increasing the capacity for protein folding and removal of unfolded proteins by the ER associated degradation (ERAD) system. In order to analyse the influence of ERAD on production of a human IgG, we disrupted ERAD at different stages by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…When using cellular engineering to improve heterologous protein production, it is also useful to gain understanding of the underlying changes in strains with interesting secretion phenotypes. To gain more insight in how some of the overexpressed folding factors influence the progression of the antibody through the cell, we selected five strains for use in a cellular clearance assay as described in De Ruijter and Frey [ 12 ]. The strains were as follows: the two genetic strain backgrounds; wt and Δopi1, the highest producers from both backgrounds; wt with the CPR5 -P KAR2 plasmid, and Δopi1 with the CPR5 -P GPD plasmid, and finally one of the strains with a negatively affecting gene combination: Δopi1 with the KAR2 -P GAL1 and the LHS1 -P GAL1 plasmids.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When using cellular engineering to improve heterologous protein production, it is also useful to gain understanding of the underlying changes in strains with interesting secretion phenotypes. To gain more insight in how some of the overexpressed folding factors influence the progression of the antibody through the cell, we selected five strains for use in a cellular clearance assay as described in De Ruijter and Frey [ 12 ]. The strains were as follows: the two genetic strain backgrounds; wt and Δopi1, the highest producers from both backgrounds; wt with the CPR5 -P KAR2 plasmid, and Δopi1 with the CPR5 -P GPD plasmid, and finally one of the strains with a negatively affecting gene combination: Δopi1 with the KAR2 -P GAL1 and the LHS1 -P GAL1 plasmids.…”
Section: Resultsmentioning
confidence: 99%
“…The plasmid for the IgG gene integration was achieved as follows: a fragment from pEK5 plasmid [ 12 ], containing genes for heavy and light chain each under GAL1-promoter, was amplified with PCR by using the oligonucleotides 1 and 2. These oligonucleotides contained complementary 5′ ends to the pRS303N-plasmid [ 66 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that excessive protein production could negatively affect protein folding due to deficiency in chaperones and saturation of the secretion machinery (Dulermo et al 2017). It has been postulated that folding, maturation, and intracellular transportation constitute the main bottlenecks of the overall process of recombinant protein production (Gasser et al 2007a; de Ruijter and Frey 2015; Puxbaum et al 2015; Tang et al 2015). Depending on the specific properties of the targeted polypeptide, i.e., primary and secondary structure, oligomerization, glycosylation, and the ultimate destination, different phenomena may limit the overall efficiency of the secretory protein synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…trigger the unfolded protein response/ER-associated degradation). [40][41][42][43][44] When a protein of interest should not accumulate to satisfactorily high levels, one could apply various genetic manipulations, including chemical mutagenesis, activation tagging, 45 and targeted/untargeted overexpression (for example, FOX hunting) 46 to the transgenic line of interest and screen for individuals with high expression levels, like used in bacterial engineering. 47 The factors identified by such approaches can also be incorporated into other large-scale plant expression systems, via CRISPR/Cas9-targeted mutagenesis or overexpression of endogenous factors.…”
mentioning
confidence: 99%